2010
DOI: 10.3928/01477447-20091124-04
|View full text |Cite
|
Sign up to set email alerts
|

Floating Knee Injuries: A High Complication Rate

Abstract: Floating knee injuries are usually associated with complications and mortality, regardless of the treatment regimen. Orthopedic surgeons typically recommend various treatment regimens, especially aggressive and early stabilization of both femoral and tibial fractures. Some authors have reported that the complication and mortality rates remain high regardless of the treatment regimen used. The purpose of this retrospective study was to review the long-term results of treatments for floating knee injuries perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
3
36
2
3
Order By: Relevance
“…Kao et al14) summarized the indications of surgical treatment and concluded that patients with closed fractures or open type I or II fractures were treated according to the fracture site. Femoral fractures around the cervicotrochanteric area were fixed under traction with dynamic hip screws, dynamic compression screws, or cannulated screws on a fracture table.…”
Section: Discussionmentioning
confidence: 99%
“…Kao et al14) summarized the indications of surgical treatment and concluded that patients with closed fractures or open type I or II fractures were treated according to the fracture site. Femoral fractures around the cervicotrochanteric area were fixed under traction with dynamic hip screws, dynamic compression screws, or cannulated screws on a fracture table.…”
Section: Discussionmentioning
confidence: 99%
“…Kao et al in fact did not comment on vascular insult in their report on 419 patients. 39 Fraser et al reported an incidence of 7% (16 of 222 patients). 3 …”
Section: Discussionmentioning
confidence: 99%
“…39 High rates of complications have been described. 40 In such injuries it is difficult to achieve good functional results due to important soft-tissue injuries and associated injuries, often resulting in life-threatening trauma of the head, chest, and abdomen or amputation of the limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations